Estimating systemic risk for non-listed Euro-area banks - Engle, Robert F.; Emambakhsh, Tina; Manganelli, Simone; Parisi, Laura; Pizzeghello, Riccardo (Journal of Financial Stability, 2024)
SRISK is a measure of a firms' systemic risk contribution that is computed using its listed stock market price. SRISK measurement is extended and applied to firms that do not have listed equity. A mapping from balance sheet characteristics to SRISK for listed firms is applied to SRISK for unlisted European banks. The mapping is validated by comparing SRISK measures for unlisted banks with their losses in European bank stress-testing.